Emerging degrader technologies engaging lysosomal pathways. (11th October 2022) - Ding, Yu; Xing, Dong; Fei, Yiyan; Lu, Boxun
Abstract : ATTECs and several other emerging degrader technologies hijacking the lysosomal pathways greatly expand the spectrum of degradable targets and provide new opportunities for targeted drug discovery. Abstract : Targeted protein degradation (TPD) provides unprecedented opportunities for drug discovery. While the proteolysis-targeting chimera (PROTAC) technology has already entered clinical trials and changed the landscape of small-molecule drugs, new degrader technologies harnessing alternative degradation machineries, especially lysosomal pathways, have emerged and broadened the spectrum of degradable targets. We have recently proposed the concept of autophagy-tethering compounds (ATTECs) that hijack the autophagy protein microtubule-associated protein 1A/1B light chain 3 (LC3) for targeted degradation. Other groups also reported degrader technologies engaging lysosomal pathways through different mechanisms including AUTACs, AUTOTACs, LYTACs and MoDE-As. In this review, we analyse and discuss ATTECs along with other lysosomal-relevant degrader technologies. Finally, we will briefly summarize the current status of these degrader technologies and envision possible future studies.